Facies Analysis and Sequence Stratigraphy of the Zubair Formation in the Kifl oil field, Central of Iraq - Al-Zaidy, Aiad Ali Hussien (Iraqi Journal of Science, 2019)
The Zubair Formation is the most significant sandstone reservoir in Iraq which deposited during the Barremian. The study area is located in the central part of Iraq at the Kifl oil field, in the northern part of the Mesopotamian Zone.The petrographic study showed that quartz mineral is the main component of the sandstone in Zubair Formation with very low percentage of feldspar and rare rock fragments to classified as quartz arenite sandtone. There are five lithologic changes (lithofacies) that have characterized the studied succession: - well sorted quartz arenite, poorly sorted quartz arenite, poorly sorted graywacke, sandy shale, and shale. These lithofacieses were deposited in the deltaic environments as three associated facies [delta plane, delta front and distributary channel]. The different lithofacies contributed to division of the Zubair Formation into three distinct rock units, which had been used in interpreting and distributing the suggested environments. The lower part of Zubair Formation is characterized by wide spread mud - dominated delta plain associated facies. The presence of the delta plain facies overlaying the unconformity surface (SB1) refer to the transgressive system tract (TST). This stage ended with occurrence of the channel fill deposit to mark a high-stand system tract (HST). This stage has ended with the delta plain facies again to mark a high-stand system tract (HST). The fluctuation point between the TST and HST is represented by a maximum flooding surface.The middle part of Zubair Formation is characterized by moderate to well sorted quartz arenite sandstone with bands of the shale overlaying the sand body. This succession was deposited in the delta front environment with steps of sea level stillstand during the high stand stage. The HST in this part ended with sea level rise (TST) to mark the upper part of the Zubair Formation with appeared the delta front facies.While the upper part is represented by alternative of delta front and delta plain facies as four cycles. The sea level rise was marked the end of this stage when deposition the upper part of Zubair Formation, and the beginning of deposition the Shuaiba Formation as shallow marine carbonate.